Strategies for Overcoming Psychological Barriers of Mad’u in Receiving Da’wah Messages at Al-Muchlisin Mosque - Putri, Zulfa Nazira; N, Nasichah; A, Azkiya; Aisyar, Muhammad Javier (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze effective da’wah strategies based on the mental and spiritual readiness of mad’u (the audience). Using a qualitative approach through a literature study, the research finds that the mental and spiritual conditions of mad’u greatly influence their receptiveness to da’wah messages. Mad’u with good mental stability and strong spiritual engagement tend to be more open to da’wah, while those experiencing psychological pressure or having low religious involvement are more likely to reject or disregard the message. The findings also highlight the importance of a personal and empathetic da’wah approach, in which da’i (preachers) with high emotional intelligence are better able to adapt da’wah methods to the conditions of mad’u. This study proposes the development of da’wah strategies that take into account the mental and spiritual readiness of mad’u, emphasizing empathetic and educational approaches. The implication of this research is the need to enhance understanding of mad’u psychology and to develop the emotional intelligence of da’i in order to improve the effectiveness of da’wah.